High-power deep-UV laser for improved and novel experiments on hydrogen - Burkley, Zakary Neumann, author; Yost, Dylan, advisor; Roberts, Jacob, committee member; Bradley, Mark, committee member; Menoni, Carmen, committee member (Colorado State University. Libraries, 2019)
This dissertation details the design, performance, and cavity enhancement of a novel, high-power coherent 243.1 nm laser system, and through simulations, its ability to trap hydrogen in a magic wavelength optical trap. This wavelength of light is necessary to address the 1S–2S two-photon transition in hydrogen, and the primary motivation behind development of this laser system is obtaining high enough 243.1 nm powers for two-photon cooling of hydrogen. Due to the light mass of hydrogen, high precision spectroscopy of hydrogen is limited by unwanted motional effects, which could be mitigated with laser cooling and confinement in an optical trap. Besides laser cooling, a high power deep-UV laser system at this wavelength has great utility for improving spectroscopy of hydrogen and other exotic simple systems. High-power fiber lasers from 1-1.2 µm have flourished as a result of advances in ytterbium(Yb)-doped fiber amplifiers. In addition, high-power Yb-fiber lasers between 975-980 nm have also been developed—a notable accomplishment due to gain competition in the > 1 µm spectral region. These systems initially lacked sufficiently narrow spectral bandwidth for efficient harmonic generation, motivating further development since there is significant interest in frequency doubling and quadrupling these sources to produce coherent blue radiation and deep-UV radiation. Here, we generate coherent, high-power deep-UV radiation through frequency quadrupling of a high-power, highly coherent Yb-fiber amplifier at 972.5 nm. The Yb-fiber amplifier system consists of a frequency stabilized master oscillator power amplifier (MOPA) that can be referenced to a coherent frequency comb. This MOPA can be amplified to > 10 W of narrow linewidth power at 972.5 nm in the Yb-fiber amplifier. This is a technically challenging and notable result for this wavelength as gain is much more readily obtained in Yb-doped fibers at the absorption/emission cross-section peak near 975 nm and in the > 1 µm spectral region where the emission cross-section is much larger than the absorption cross-section. This system successfully combated unwanted gain at these wavelengths by using a relatively short (≈ 10 cm), angle-polished Yb-fiber with a large core-cladding ratio, along with aggressive spectral filtering and large amounts of seed power at 972.5 nm. With this narrow linewidth Yb-fiber amplifier, efficient frequency conversion of high power 972-976 nm radiation to 243-244 nm radiation is possible through intracavity doubling. Through successive resonant doubling stages, this system demonstrates > 1 W of highly stable, continuous-wave (CW) 243.1 nm power. To the author's knowledge, this is a record amount of CW deep-UV power below 266 nm, and is made possible thanks to advances in the production of a relatively new non-linear crystal for robust deep-UV generation, cesium lithium borate (CLBO). The precise frequency control of this radiation is established via excitation of the 1S–2S transition in hydrogen, and the viability for two-photon laser cooling on this transition is shown through enhancement of this power to > 30 W of intracavity power in a deep-UV enhancement cavity. At these powers, UV-induced mirror degradation was observed and mitigated by flushing the enhancement cavity mirrors with ultra-pure oxygen. With these powers, rapid two-photon laser cooling of a hydrogen atomic beam approaches reality. The 243.1 nm powers offered by this laser system also offer unique methods for capturing hydrogen in an optical trap. Explored via simulations, single optical scatter capture of hydrogen in a magic wavelength dipole trap is demonstrated, promising exciting new avenues for high precision spectroscopy of hydrogen.
Keywords: high power Yb-fiber amplifier; laser cooling; hydrogen spectroscopy; high power deep-UV laser